METODE PEMULIHAN MENTAL ILLNESS OLEH TIM RELAWAN TERHADAP ORANG DENGAN GANGGUAN JIWA DI KECAMATAN BANGUN PURBA - Harahap, Nurul Atika Roismaini; Kamalia, Kamalia (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The aim of this research is to find out how to recover mental health for people with mental disorders. The research subjects consisted of 30 subjects owned by the community health center. This research was conducted using data collection methods using interviews. To understand the percentage, data analysis uses qualitative techniques. Research findings show that there are mental recovery methods for people with mental disorders provided by experts such as Doctors, Health Center Midwives, Babinsa and Babinkamtibmas.